Pertumbuhan dan Kadar Alkaloid Tanaman Leunca (Solanum americanum Miller) pada Beberapa Dosis Nitrogen - Marchella Putriantari; Edi Santosa (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2014)
ABSTRACTLeunca fruit is indigenous vegetable and widely used as vegetables mainly in West Java. In order to improve productivity and quality, several levels of nitrogen was used. The objective of the experiment was to determine the effect of nitrogen level on growth and productivity, and on the alkaloid levels. The experiment was conducted at Leuwikopo Experimental Station IPB in December 2013 - April 2014. Experiment was arranged in a Randomized Complete Block Design with single factor and four replications. Nitrogen fertilizer consisted of four levels, i.e., 0 kg N ha-1, 60 kg N ha-1, 120 kg N ha-1, and 180 kg N ha-1. The results showed that growth and productivity were affected by nitrogen application. The highest productivity of Leunca was obtained by nitrogen fertilizer at rate of 180 N ha-1, and the highest alkaloid content was produced by plant treated with 60 kg N ha-1. The highest productivity of fruits was 18 445 kg ha-1.Key words: alkaloid, indigenous vegetable, productivity, Solanum nigrum, nitrogen dosage ABSTRAKBuah leunca merupakan sayuran indigenous terutama bagi masyarakat Jawa Barat. Dalam rangka meningkatkan produktivitas dan kualitas buah leunca, perlu dilakukan kajian budidaya khususnya pemupukan. Penelitian ini bertujuan menentukan dosis pupuk nitrogen terbaik untuk meningkatkan pertumbuhan dan produktivitas tanaman leunca, serta mengkaji pengaruh pupuk nitrogen terhadap kadar alkaloid tanaman leunca. Percobaan ini dilaksanakan di Kebun Percobaan Leuwikopo IPB pada bulan Desember 2013 - April 2014. Percobaan ini menggunakan Rancangan Kelompok Lengkap Teracak satu faktor dengan empat ulangan. Faktor dosis pupuk nitrogen terdiri atas empat taraf, yaitu tanpa pupuk N, 60 kg N ha-1, 120 kg N ha-1, dan 180 kg N ha-1. Hasil penelitian menunjukkan bahwa pertumbuhan dan produktivitas tanaman terbaik dihasilkan oleh perlakuan dosis pupuk nitrogen 180 kg N ha-1. Kadar alkaloid tertinggi dihasilkan tanaman dari perlakuan dosis pupuk nitrogen 60 kg N ha-1. Produktivitas buah leunca mencapai 18 445 kg ha-1.Kata kunci: alkaloid, produkvitas, sayuran indigenous, Solanum nigrum, dosis nitrogen